The optical depth sensor (ODS) for column dust opacity measurements and cloud detection on martian atmosphere - Toledo, D; Rannou, P; Pommereau, J; Foujols, T (Springer Verlag, 2016)
A lightweight and sophisticated optical depth sensor (ODS) able to measure alternatively scattered flux at zenith and the sum of the direct flux and the scattered flux in blue and red has been developed to work in martian environment. The principal goals of ODS are to perform measurements of the daily mean dust opacity and to retrieve the altitude and optical depth of high altitude clouds at twilight, crucial parameters in the understanding of martian meteorology. The retrieval procedure of dust opacity is based on the use of radiative transfer simulations reproducing observed changes in the solar flux during the day as a function of 4 free parameters: dust opacity in blue and red, and effective radius and effective width of dust size distribution. The detection of clouds is undertaken by looking at the time variation of the color index (CI), defined as the ratio between red and blue ODS channels, at twilight. The retrieval of altitude and optical depth of clouds is carried out using a radiative transfer model in spherical geometry to simulate the CI time variation at twilight. Here the different retrieval procedures to analyze ODS signals, as well as the results obtained in different sensitivity analysis are presented and discussed.